Economic Performance and Human Capital Eligibility Requirements of Immigrants Admitted Through the Diversity Immigrant Visa Program - Kelly, Claudia Smith; Solomon, Blen (Journal of Applied Business and Economics, 2020)
This paper focuses on the economic performance of immigrants admitted through the diversity immigrant visa program otherwise known as the DV lottery. The question of interest is: does the human capital eligibility requirement improve the economic performance of diversity immigrants compared to immigrants in other admission categories? Using the first round of the New Immigrant Survey, the results indicate that diversity immigrants were less likely to be home owners than immigrants admitted as spouse of U.S. citizens. In addition, diversity immigrants were less likely to work for pay than immigrants admitted through the employment admission category.